2019
DOI: 10.1103/physrevlett.123.131602
|View full text |Cite
|
Sign up to set email alerts
|

Critical Look at β -Function Singularities at Large N

Abstract: We propose a self-consistency equation for the β-function for theories with a large number of flavours, N , that exploits all the available information in the Wilson-Fisher critical exponent, ω, truncated at a fixed order in 1/N . We show that singularities appearing in critical exponents do not necessarily imply singularities in the β-function. We apply our method to (non-)abelian gauge theory, where ω features a negative singularity. The singularities in the β-function and in the fermion mass anomalous dimen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…[63][64][65] it was shown that renormalizable field theories can be made asymptotically free with respect to all couplings (including the quartic couplings λ abcd ) if embedded in a theory with a (semi-)simple gauge group and with a complex field content. The field content can be made simpler in asymptotically safe extensions of the SM, which, however, present some challenges [66,67]. The scenario described in Sec.…”
Section: Complexity Of Uv-completionsmentioning
confidence: 99%
“…[63][64][65] it was shown that renormalizable field theories can be made asymptotically free with respect to all couplings (including the quartic couplings λ abcd ) if embedded in a theory with a (semi-)simple gauge group and with a complex field content. The field content can be made simpler in asymptotically safe extensions of the SM, which, however, present some challenges [66,67]. The scenario described in Sec.…”
Section: Complexity Of Uv-completionsmentioning
confidence: 99%
“…1 The analysis based on resummation has been recently challenged in Ref. [16] but without conclusively disproving the existence of a fixed point [17], while studies on the lattice are still inconclusive [18]. In this work we will assume that the presence of a pole in the large N f expansion is a sign of a genuine UV fixed point.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been of paramount interest to identify fundamental, i.e., ultraviolet (UV) complete, quantum field theories in which the cutoff can be removed-first asymptotically free [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], and more recently, asymptotically safe gauge-Yukawa theories. See also [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] (with potential caveats discussed in [59][60][61]) for asymptotically safe gauge-Yukawa theories from resummation at a large number of matter fields and [62] for a recent review including lattice results.…”
Section: Motivationmentioning
confidence: 99%